2015
DOI: 10.1111/imr.12301
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ligase Itch in immune regulation and beyond

Abstract: Itch or itchy E3 ubiquitin ligase was initially discovered by genetic studies on the mouse coat color changes, and its deletion results in an itchy phenotype with constant skin scratching and multi-organ inflammation. It is a member of the homologous to E6-associated protein C-terminus (HECT)-type family of E3 ligases, with the protein-interacting WW-domains for the recruitment of substrate and the HECT domain for the transfer of ubiquitin to the substrate. Since its discovery, numerous studies have demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 224 publications
(332 reference statements)
0
47
0
Order By: Relevance
“…Beyond the essential function in the control of immune system, Itch is also implicated in other biological processes, including development, tumorigenesis, and stress responses [45,46]. Most of these findings were made in an Itch-deficient context, for example, the Itch À/À Itchy mice.…”
Section: Activation Of Itch Promotes Neuronal Migration In the Develomentioning
confidence: 99%
“…Beyond the essential function in the control of immune system, Itch is also implicated in other biological processes, including development, tumorigenesis, and stress responses [45,46]. Most of these findings were made in an Itch-deficient context, for example, the Itch À/À Itchy mice.…”
Section: Activation Of Itch Promotes Neuronal Migration In the Develomentioning
confidence: 99%
“…Members of the NEDD4 family include WWP2, WWP1, ITCH, and NEDD4-1 and these E3 ligases target for destruction key signaling molecules and transcription factors (Aki et al, 2015; Buetow and Huang, 2016; Chen et al, 2014; Scheffner and Kumar, 2014; Zhi and Chen, 2012). Abnormal activities of NEDD4 E3 ligases are connected to cancer, immune disorders, and other diseases (Aki et al, 2015; Broix et al, 2016; Buetow and Huang, 2016; Chen et al, 2014; Scheffner and Kumar, 2014; Zhi and Chen, 2012). The NEDD4 family proteins each contain an N-terminal C2 domain followed by two to four WW domains and culminate in a C-terminal catalytic HECT domain (Figure 1A and Figure S1A) (Buetow and Huang, 2016).…”
mentioning
confidence: 99%
“…10 Further evidence showed that tissue alterations such as abnormal dermal proliferation and tumor proliferation first identified in itchy mice, manifest similarly in humans with Itch polymorphisms. 9,11,12 These findings justify further patho-physiological analyses of itchy mice and identifications of novel physiologic pathways affected by ITCH.…”
Section: Introductionmentioning
confidence: 75%
“…Both helper T cells 9 and macrophages 32 are alternatively polarized in itchy mice. The biased differentiation of leukocytes in itchy mice may account for the pathologic female reproductive function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation